Evaluation of tenosynovitis in patients with seronegative rheumatoid arthritis using microvascular flow imaging. (December 2022) - Wang, Junkui; Wu, Zhibin; Wang, Miao; Qi, Qinghua; Song, Qingshan; Sun, Bingfang; Li, Caiyun; Dong, Yu
Highlights: MVFI detects blood flow in the tendon synovial sheaths of SNRA patients with a higher sensitivity and increases the blood flow display rate. MVFI  can indicates disease activity. MVFI facilitates diagnosis of active inflammation at an early stage. Abstract: Objectives: The purpose of this research was investigate the potential use of MVFI (microvascular flow imaging) in the assessment of tenosynovitis in cases with SNRA (seronegative rheumatoid arthritis). Methods: Fifty-six SNRA cases and 20 HCs (healthy controls) were enrolled, and all of them were subjected to ultrasonographic examination of the compartments I-VI of the extensor tendons of the wrist, flexor carpi radialis and flexor tendons of the five digits. Each tendon synovial sheath was semi-quantitatively scored by GS (gray-scale) ultrasound, PD (power Doppler) ultrasound, and MVFI. The PD and MVFI scores for each tendon synovial sheath were added up for each patient to get the total scores. GS scores, PD scores, and MVFI scores of tendon synovial sheaths were compared between the two groups. The correlations of total PD scores and total MVFI scores with DAS28 (disease activity scores in 28 joints), ESR (erythrocyte sedimentation rate), and CRP (C-reactive protein) were analyzed. Results: (1) In the HC group (480 tendons), GS revealed abnormalities in 29 (6.04%) tendon synovial sheaths. The GS score was 1.03 ± 0.18 with the predominance of GS grade 1 (96.55%). In the SNRA group (1, 344 tendons), GS detected abnormalities in 418 tendon synovial sheaths (31.10%). The GS score was 1.97 ± 0.53 with the predominance of GS grade 2 (71.77%). There were significant differences in the GS examination rate and grade for tenosynovitis between the two groups ( P  < 0.05). (2) In the SNRA group, involvement of the extensor carpi ulnaris in the 6 th dorsal compartment was the most common among all extensor tendons; the flexor tendon of the third digit was the most commonly affected among all flexor tendons. (3) In the HC group, the MVFI and PD scores were 0 for tendon synovial sheaths upon GS examination. In the SNRA group, the blood flow display rate of abnormal tendon synovial sheaths indicated by GS was 83.49% and 64.59% upon MVFI and PD, respectively. The results of the two imaging techniques were significantly different ( P  < 0.05). The blood flow grade of abnormal tendon synovial sheaths indicated by GS was significantly different between MVFI and PD ( P  < 0.05), which was higher upon MVFI than PD. (4) The total MVFI score and the total PD score in the SNRA group were correlated positively with CRP, ESR and DAS28 ( P  < 0.05). Conclusion: MVFI is a more sensitive way in detection of blood flow in the tendon synovial sheaths of SNRA cases, which may be used in clinic to evaluate disease activity and tenosynovitis in SNRA cases.